Determination of nutrient content, β-carotene, and antioxidant activity of Moringa oleifera extraction using organic solution - Haroen, Ucop; Syafwan,; Kurniawan, Kiki; Budiansyah, Agus (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The research was conducted to determine β-carotene and antioxidant activities and screening of phytochemical substances of Moringa oleifera extraction using organic solution. Materials and Methods: 550 gm of M. oliefera leaf flour was macerated. This research was conducted by laboratory experiments using the maceration method. The extraction was performed using three kinds of solvents, which are n-hexane, ethyl acetate, and methanol; for 3 x 24 h, they were concentrated with a rotary evaporator. Then, the flavonoid, phenolic, β-carotene isolation, and antioxidant tests were conducted using the 2,2-diphenyl-1-picrylhydrazyl on each fraction (n-hexane, ethyl acetate, and methanol). Results: The results of weighing each concentrated extract from the maceration process of each fraction (n-hexane, ethyl acetate, and methanol) were 12.67, 35.67, and 49.29 gm, with the total phenolic content (1.4595 ± 0.361, 46.5489 ± 1.832, and 39.74574 ± 0.786) and total flavonoid content of each fraction (3.3056 ± 0.039, 58.6389 ± 2.051, and 48.9056 ± 0.0809), respectively. The antioxidant activity test on the crude extract from the ethyl acetate fractionation showed that the IC50 value was 30.309 mg/ml. The ethyl acetate fraction has a high total phenolic and flavonoid content. The results of the isolation of β-carotene from M. oleifera leaf flour were 0.4798 gm, or equivalent to 0.956% carotenoids. Conclusions: Based on the results of the research, M. oleifera leaves are identified to have a fairly high antioxidant activity, which is 30.309 mg/ml, resulting from the potential compounds in M. oleifera leaves that function as inhibitors of antioxidant activity, which are the groups of phenolic and flavonoid compounds. J. Adv. Vet. Anim. Res., 9(2): 246–254, June 2022 http://doi.org/10.5455/javar.2022.i590